Leadership In Change Management from An Islamic Perspective - Habib, Muhammad Fahmi (Utami Publisher, 2024)
All types of organisations require leadership, which is an essential component of the management process. By influencing and directing others, leaders organise and utilise available resources to maximise employee performance. Any attempt made by a person to influence the behaviour of a person or group is referred to as leadership. trying to influence this behaviour to meet personal or organisational goals. Since leadership is a key activity in achieving organisational goals, it has a significant impact on how well an organisation performs. As Allah states in Surah Al-A'raf verse 129, leadership should be positioned in every mission (task) of life and devotion (worship) of every person as a successor in his country. Change is happening rapidly nowadays, and every organisation is in need of leadership.